Late Vitamin K Deficient Bleeding in 2 Young Infants – Renaissance of a Preventable Disease - Siauw, C.; Wirbelauer, J.; Schweitzer, T.; Speer, C. P. (Zeitschrift für Geburtshilfe und Neonatologie, 2015)
Introduction: Late vitamin K deficiency bleeding in young infants is a rare disorder which occurs almost exclusively in breast-fed infants who did not receive proper vitamin K prophylaxis at birth and who might additionally suffer from cholestasis. Its impact on morbidity is high since in 50% of the cases it presents with intracranial hemorrhage with a mortality rate of 20% and life-long neurologic sequelae in 30% of the affected infants. Case reports: 2 male infants were both admitted to our unit at the age of 5 weeks with subdural hematoma with midline shift due to late vitamin K deficiency bleeding. Both infants did not receive the recommended Vitamin K prophylaxis in Germany. One patient presented with cholestatic jaundice on admission as an additional risk factor.Discussion: Parents who in the apparent best interest for their children refuse the recommended and well established vitamin K prophylaxis at birth leading to the reappearance of late vitamin K deficiency bleeding. These parents also tend to refuse routine immunizations of childhood in later life, which not only have an impact on their own child but might bear a risk for the whole community.Conclusion: It is the responsibility of health-care takers to show increased awareness to the growing number of parents refusing vitamin K prophylaxis at birth and educate them properly about the devastating consequences of late vitamin K deficiency bleeding.
Keywords: late vitamin K deficiency bleeding; infants; prophylaxis; intracranial hemorrhage; parental refusal